The plundering of libraries and archives of Lima during the Chilean occupation between 1881 and 1883 - Carcelén Reluz, Carlos (2014)
The War of the Pacific, sometimes referred to as the Saltpeter War, not only brought destruction and death, but also meant the plundering of thousands of books, documents, instruments and scientific, artistic and archaeological collections; in short, it was vanished any trace of a historical memory created and gathered over the course of the centuries in the old Viceroyalty of Peru’s capital. This memory partly summed up Peruvians historical identity and the legacy that served as a basis to plan a Republic that despite its problems was building a nation. We present in this paper the progress made by a major research being developed now a days, which constitutes an attempt to recover a memory and an identity snatched way that unfortunately neither the victors nor the vanquished of this bitter and distant war -but still very fresh in people’s memory- have accepted.